2021
DOI: 10.1177/0267658321993873
|View full text |Cite
|
Sign up to set email alerts
|

The computation and suspension of presuppositions by L1-Mandarin Chinese L2-English speakers

Abstract: The Interface Hypothesis proposes that second language (L2) learners, even at highly proficient levels, often fail to integrate information at the external interfaces where grammar interacts with other cognitive systems. While much early L2 work has focused on the syntax–discourse interface or scalar implicatures at the semantics–pragmatics interface, the present article adds to this line of research by exploring another understudied phenomenon at the semantics–pragmatics interface, namely, presuppositions. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Our results showed that (a) L2 speakers were more accurate than L1 speakers in their overall reading comprehension, (b) that entailments were easier to retrieve than presuppositions or unstated information, and (c) that L2 speakers' performance did not seem to correlate with their level of proficiency. Result (b) is in line with previous findings that demonstrated some variation in computing different types of meaning (Feng, 2022;Feng and Cho, 2019). Conversely, results (a) and (c) are surprising, for which some speculative explanations were provided in Section 5.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our results showed that (a) L2 speakers were more accurate than L1 speakers in their overall reading comprehension, (b) that entailments were easier to retrieve than presuppositions or unstated information, and (c) that L2 speakers' performance did not seem to correlate with their level of proficiency. Result (b) is in line with previous findings that demonstrated some variation in computing different types of meaning (Feng, 2022;Feng and Cho, 2019). Conversely, results (a) and (c) are surprising, for which some speculative explanations were provided in Section 5.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, in some of the above studies, fine-grained differences between L1 and L2 speakers emerged. Feng (2022) found that L1 English speakers and L1-Mandarin Chinese L2-English speakers generated the inference of the presupposition trigger stop in affirmative and negated sentences at similar rates in both conditions, yet L2 speakers were significantly slower than L1 speakers in processing the inference. Furthermore, L2 speakers were less likely to suspend, that is, more likely to fail to retrieve, presuppositions than L1 speakers.…”
Section: Literature Reviewmentioning
confidence: 86%
See 2 more Smart Citations
“…To create reported speech, syntactic rephrasing is often carried out on the part of the speaker that may not be problematic to an L2 speaker with a high level of competency; however, the processes Günthner referred to as ‘decontextualising’ and ‘recontextualising’ speech necessarily go beyond purely linguistic mechanisms, calling upon their interface with other cognitive systems. For example, the generation and processing of presuppositions in a sentence, which rely on cognitive systems as well as linguistic ones, have been shown to be different in L1 and L2 adults (Cho, 2017; Evans et al, 2018; Feng, 2021). In this regard, Wong (2010, p. 2932) argues that[…] what language is about goes beyond lexicon and grammar to include non-formal features like conversational routines, frequency of use of certain expressions, the avoidance of certain ways of speaking, pragmemes, etc., which can only be satisfactorily explained with reference to culture.With regard to Bakhtin’s concept of DVD, this article illustrates that L2 indirect reports do not always abide by a fair paraphrase (i.e., the retelling of what the original speaker said) of the original speaker, for the learners can infuse their subjective manipulation from several sources into the original speaker’s discourse.…”
Section: Introductionmentioning
confidence: 99%